Balancing market design and opportunity cost - the Swiss case - Moritz Schillinger (University of Basel, Center of Business and Economics (WWZ), 2019)
In 2017, the Swiss electorate voted to transition the Swiss energy system towards energy efficiency and renewable energy resources. This transition entails many changes to the existing energy technologies and the supporting markets. In particular, this paper focuses on the Swiss electricity balancing markets and their adaptation in the context of the energy transition. I use an operational model for a set of Swiss hydropower plants to quantify the opportunity costs of balancing provision for hydropower under the past, current, and future Swiss balancing market designs. My results show that compared to the former balancing market design, significant cost savings can be achieved by the planned modifications. In addition, I show how the opportunity cost dynamics may change in the future with an increasing share of variable renewable energy in the system.
Keywords: 330; Energiehandel; Energiemarkt; Mechanismus-Design-Theorie; Wasserkraft; Opportunitätskosten; Schweiz